2019
DOI: 10.3390/en12244609
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Torrefaction Temperature on Hydrophobic Properties of Waste Biomass from Food Processing

Abstract: The annual potential of waste biomass production from food processing in Europe is 16.9 million tonnes. Unfortunately, most of these organic wastes are utilized without the energy gain, mainly due to the high moisture content and the ability to the fast rotting and decomposition. One of the options to increase its value in terms of energy applications is to valorize its properties. Torrefaction process is one of the pre-treatment technology of raw biomass that increases the quality of the fuel, especially in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 54 publications
7
32
0
Order By: Relevance
“…The impact of thermal processing on the physicochemical properties of many popular types of biomass is known. The studies about biomass torrefaction and pyrolysis [10][11][12][13][14][15] showed that the higher temperature of the biomass processing improves its thermal properties. The biochar is characterized by higher heating value, lower moisture content, lower volatile matter content, and improved hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of thermal processing on the physicochemical properties of many popular types of biomass is known. The studies about biomass torrefaction and pyrolysis [10][11][12][13][14][15] showed that the higher temperature of the biomass processing improves its thermal properties. The biochar is characterized by higher heating value, lower moisture content, lower volatile matter content, and improved hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, bioenergy is a tool to improve the economic and environmental sustainability of agricultural sector. A potential source of biomass is represented by the residues of wheat, spelt (Triticum ssp., L.), and maize (Zea mays L.) [4,5]. Indeed, the EU-28 produced yearly 152 Mt wheat and spelt [6], and chaff, a heterogeneous mixture of glumes, dust, short straw pieces, broken grain seeds, and weed seeds represents a potential biomass of 38 Mt year −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Torrefaction is a process of thermal valorization of solid fuel in order to enhance its fuel properties subsequently allowing low-grade fuels, such as biomass, to become a tradable commodity [4]. It is a process that is considered to improve the logistics and handling of the upgraded fuel [5][6][7][8][9][10] and make it more suitable for final use, such as co-firing [11][12][13] or gasification [14][15][16]. Torrefaction is 2 of 19 sometimes called slow pyrolysis and it typically takes place at temperatures between 250 • C and 300 • C with residence times ranging between 10 min and 60 min [4,[17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%